(3GdjghO bGadI GdTQ ai GdJGQjNs - (3eUWai, eMeO eMeO EHQGgjes ((3GdEScfOQjI(B[(3eUQ(B]s (3OGQ GdgfGAs, 2008)
(3ai gPG GdcJGH LhdI TGedI, dbUI GdjghO ef HOGjJgG ajeG bHd GdejdGO, MJi YUQfG GdMOjK, h ajeG fQi KdGK eMWGJ, LSOJ GdJUhQ GdfgGFi ddjghO, h cja jchf GdMSe JLGgges
(3bGFeI HHdjhLQGajI(B: (3U(B. 341- 342s
3 11 15
Keywords: (3GdUgjhfjIs; (3GdjghOs; (3GdjghOs -- (3JGQjNs